Разработка метода прогноза и исследование политерм кристаллизации льда в системах Pb(SO₃NH₂)₂ – LiSO₃NH₂ – H₂O И Pb(SO₃NH₂)₂ – этиленгликоль – H₂O - Коваленко, Д. Е. (НТУ "ХПИ", 2007)
Розраховані за оригинальною методикою, експериментально досліджені та побудовані політерми замерзання льоду в зазначених системах. Добра відповідність прогнозу та експерименту продемонстрована також для довідникових даних про поле кристалізації льоду системи MgCl₂– NaCl – H₂O

The polytherms of freezing of ice of the systems have been calculated using original method, experimentally researched and plotted. Good agreement between the forecast and experiment has been shown also for the handbook data about the field of crystallization of ice of the system MgCl₂– NaCl – H₂O
Keywords: диаграммы плавкости; термодинамический расчет; фазовые диаграммы; доэвтектические концентрации; математическая модель; методика измерений; политермы замерзания льда